Guidelines for usable cybersecurity: past and present - Nurse, J; Creese, S; Goldsmith, M; Lamberts, K (IEEE, 2011)
Usability is arguably one of the most significant social topics and issues within the field of cybersecurity today. Supported by the need for confidentiality, integrity, availability and other concerns, security features have become standard components of the digital environment which pervade our lives requiring use by novices and experts alike. As security features are exposed to wider cross-sections of the society, it is imperative that these functions are highly usable. This is especially because poor usability in this context typically translates into inadequate application of cybersecurity tools and functionality, thereby ultimately limiting their effectiveness. With this goal of highly usable security in mind, there have been a plethora of studies in the literature focused on identifying security usability problems and proposing guidelines and recommendations to address them. Our paper aims to contribute to the field by consolidating a number of existing design guidelines and defining an initial core list for future reference. Whilst investigating this topic, we take the opportunity to provide an up-to-date review of pertinent cybersecurity usability issues and evaluation techniques applied to date. We expect this research paper to be of use to researchers and practitioners with interest in cybersecurity systems which appreciate the human and social elements of design.